TANTANGAN IMPLEMENTASI SATU DATA PENERBANGAN DAN ANTARIKSA - Difa Pramudya Utama; Lina Miftahul Jannah (Media Bina Ilmiah, 2022)
Aeronautics and Space Research Organization is a research organization under the National Research and Innovation Agency that seeks to provide research data based on Presidential Decree 39 of 2019 on One Data Indonesia in support of evidence-based policies and sustainable development goals (SGDs). In its implementation there are still many challenges in planning, collection, inspection and dissemination of data. This study aims to illustrate the challenges in facing the implementation of one data s aeronautics and space. The methods used in data collection used interviews, document studies and literature relevant to the discussion. The results of this study are the challenges faced by the Aeronautics and Space Research Organization.